Specific Plasma MicroRNA Signatures Underlying the Clinical Outcomes of Hepatitis E Virus Infection - Maria I. Costafreda; Silvia Sauleda; Mar Riveiro-Barciela; Angie Rico; Meritxell Llorens-Revull; Susana Guix; Rosa M. Pintó; Albert Bosch; Francisco Rodríguez-Frías; Ariadna Rando; Maria Piron; Marta Bes (Microbiology Spectrum, 2023)
ABSTRACT The pathogenic mechanisms determining the diverse clinical outcomes of HEV infection (e.g., self-limiting versus chronic or symptomatic versus asymptomatic) are not yet understood. Because specific microRNA signatures during viral infection inform the cellular processes involved in virus replication and pathogenesis, we investigated plasma microRNA profiles in 44 subjects, including patients with symptomatic acute (AHE, n = 7) and chronic (CHE, n = 6) hepatitis E, blood donors with asymptomatic infection (HEV BDs, n = 9), and anti-HEV IgG+ IgM− (exposed BDs, n = 10) and anti-HEV IgG− IgM− (naive BDs, n = 12) healthy blood donors. By measuring the abundance of 179 microRNAs in AHE patients and naive BDs by reverse transcription-quantitative PCR (RT-qPCR), we identified 51 potential HEV-regulated microRNAs (P value adjusted for multiple testing by the Benjamini-Hochberg correction [PBH] < 0.05). Further analysis showed that HEV genotype 3 infection is associated with miR-122, miR-194, miR-885, and miR-30a upregulation and miR-221, miR-223, and miR-27a downregulation. AHE patients showed significantly higher levels of miR-122 and miR-194 and lower levels of miR-221, miR-27a, and miR-335 than HEV BDs. This specific microRNA signature in AHE could promote virus replication and reduce antiviral immune responses, contributing to the development of clinical symptoms. We found that miR-194, miR-335, and miR-221 can discriminate between asymptomatic HEV infections and those developing acute symptoms, whereas miR-335 correctly classifies AHE and CHE patients. Our data suggest that diverse outcomes of HEV infection result from different HEV-induced microRNA dysregulations. The specific microRNA signatures described offer novel information that may serve to develop biomarkers of HEV infection outcomes and improve our understanding of HEV pathogenesis, which may facilitate the identification of antiviral targets. IMPORTANCE There is increasing evidence that viruses dysregulate the expression and/or secretion of microRNAs to promote viral replication, immune evasion, and pathogenesis. In this study, we evaluated the change in microRNA abundance in patients with acute or chronic HEV infection and asymptomatic HEV-infected blood donors. Our results suggest that different HEV-induced microRNA dysregulations may contribute to the diverse clinical manifestations of HEV infection. The specific microRNA signatures identified in this study hold potential as predictive markers of HEV infection outcomes, which would improve the clinical management of hepatitis E patients, particularly of those developing severe symptoms or chronic infections. Furthermore, this study provides new insights into HEV pathogenesis that may serve to identify antiviral targets, which would have a major impact because no effective treatments are yet available.